Past and future of a century old Citrus tristeza virus collection: a California citrus germplasm tale - Wang, Jinbo; Bozan, Orhan; Kwon, Sun-Jung; Dang, Tyler; Rucker, Tavia; Yokomi, Raymond K.; Lee, Richard F.; Folimonova, Svetlana Y.; Krueger, Robert R.; Bash, John; Greer, Greg; Vidalakis, Georgios (Frontiers in Microbiology, 2013)
Citrus tristeza virus (CTV) isolates collected from citrus germplasm, dooryard and field trees in California from 1914 have been maintained in planta under quarantine in the Citrus Clonal Protection Program (CCPP), Riverside, California. This collection, therefore, represents populations of CTV isolates obtained over time and space in California. To determine CTV genetic diversity in this context, genotypes of CTV isolates from the CCPP collection were characterized using multiple molecular markers (MMM). Genotypes T30, VT, and T36 were found at high frequencies with T30 and T30+VT genotypes being the most abundant. The MMM analysis did not identify T3 and B165/T68 genotypes; however, biological and phylogenetic analysis suggested some relationships of CCPP CTV isolates with these two genotypes. Phylogenetic analysis of the CTV coat protein (CP) gene sequences classified the tested isolates into seven distinct clades. Five clades were in association with the standard CTV genotypes T30, T36, T3, VT, and B165/T68. The remaining two identified clades were not related to any standard CTV genotypes. Spatiotemporal analysis indicated a trend of reduced genotype and phylogenetic diversity as well as virulence from southern California (SC) at early (1907–1957) in comparison to that of central California (CC) isolates collected from later (1957–2009) time periods. CTV biological characterization also indicated a reduced number and less virulent stem pitting (SP) CTV isolates compared to seedling yellows isolates introduced to California. This data provides a historical insight of the introduction, movement, and genetic diversity of CTV in California and provides genetic and biological information useful for CTV quarantine, eradication, and disease management strategies such as CTV-SP cross protection.